Pengaruh Media Simulasi Interaktif PHET Terhadap Pemahaman Konsep Fisika Siswa - Petri Reni Sasmita; Zainal Hartoyo; Nana Sutrisna (Jurnal Ilmiah Wahana Pendidikan, 2023)
This study aims to determine the effect of interactive simulation media PHET on students' ability to understand physics concepts. The research method used was an initial experimental research method with a one-group pretest-posttest design which was carried out in class XI students at one of the senior high schools in Kerinci Regency. The sampling technique used is group sampling method (cluster sampling). Data collection used the pretest and posttest to measure students' ability to understand physics concepts. The results of the effect size calculations show that the application of learning with interactive simulation media PHET has a major effect on students' ability to understand physics concepts. Thus, it can be concluded that the application of PHET interactive simulation media in learning physics has a major influence on students' ability to understand physics concepts